2008
DOI: 10.1172/jci34385
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for Costello syndrome reveals an Ang II–mediated hypertensive condition

Abstract: Germline activation of H-RAS oncogenes is the primary cause of Costello syndrome (CS), a neuro-cardio-faciocutaneous developmental syndrome. Here we describe the generation of a mouse model of CS by introduction of an oncogenic Gly12Val mutation in the mouse H-Ras locus using homologous recombination in ES cells. Germline expression of the endogenous H-Ras G12V oncogene, even in homozygosis, resulted in hyperplasia of the mammary gland. However, development of tumors in these mice was rare. H-Ras G12V mutant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
127
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(142 citation statements)
references
References 59 publications
12
127
3
Order By: Relevance
“…Moreover, Hras G12V -IRES-␤-geo mice developed age-dependent systemic hypertension, cardiac fibrosis, and vascular remodeling, particularly in homozygotes (20). There was no increase in pERK or pAKT in cardiac tissue of CC/FRHras G12V mice.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, Hras G12V -IRES-␤-geo mice developed age-dependent systemic hypertension, cardiac fibrosis, and vascular remodeling, particularly in homozygotes (20). There was no increase in pERK or pAKT in cardiac tissue of CC/FRHras G12V mice.…”
Section: Resultsmentioning
confidence: 89%
“…Accordingly, there has only been one child reported with a germline HRAS G12V mutation, which was associated with a severe form of CS that resulted in death at 18 months of age, suggesting that this mutation may not be well tolerated in humans (11). Unexpectedly, a mouse germline knock-in of a bicistronic Hras G12V allele (Hras G12V -IRES-␤-geo) was associated with a mild phenotype (20). Mice were viable, fertile, and survived normally.…”
mentioning
confidence: 99%
“…There were no reports of microdissection of the conduction system to validate Mori et al's [1996] observation of ''degeneration of the conduction system'' in which abnormalities of the conduction pathways led to the atrioventricular node. The existing mouse model does not exhibit tachycardia [Schuhmacher et al, 2008;Chen et al, 2009]. Atrial tachycardia may be a functional consequence of diastolic dysfunction in adults with HCM where increased filling pressure is associated with increased atrial stretch leading to dysrhythmia [Brembilla-Perrot et al, 1997].…”
Section: Arrhythmiamentioning
confidence: 99%
“…Congenital heart defects (CHDs), cardiac hypertrophy, usually described as hypertrophic cardiomyopathy (HCM) and arrhythmia (especially non-reentrant atrial tachycardia) were each found in approximately one-third of Costello syndrome patients. The knock-in G12V Hras mouse model, though a rare mutation in Costello syndrome, does not appear to completely recapitulate cardiac issues seen in humans [Schuhmacher et al, 2008;Chen et al, 2009].…”
Section: Introductionmentioning
confidence: 97%
“…One patient had hypertension, which was also observed in a mouse model of CS. 39 One patient had glycogen storage disease type III, as previously reported by Kaji et al, 40 accompanied by a p.G12S mutation. Bladder cancer was observed in one patient.…”
Section: Mutation Analysis In Patients With Csmentioning
confidence: 58%